DEBATES ON EDUCATION AMONG THE LATE OTTOMAN INTELLECTUALS - Hıdır ÖNÜR (Fırat University, 2019)
In this article, although it is stressed on the subjects related with education which are debated by the intellectuals in late Ottoman society, the main aim is to understand today setting up from those days. Since Second Constitution, it is still debated the same or smilar subjects by the various stratas of the society and it is often the case to make the tryouts of “reform in education”. Hence it is the indicator of the being unsuccesfull in making the use of such debates. It could be taken the cause of this failure that is the fragmentation of society into the unreconciled zones as the concequance of deepening of different lines of thought appeared by the ends of Ottomon State. However, although Ottoman intellectuals had discussed the subject of education within various lines of thought, sometimes the intelectuals in same line would have been in opposition or those being opposite lines could have been claimed same ideas. Therefore, it is important to revaluate the education debates of such era in order to dissipate todays disputes. Although the problems concerning education have changed in form, it have not changed in content. This basic idea as the ground of this paper will be elaborated by the literature review.